Georgia's perspectives for investment growth - Athina Imnaishvili; Tea Kbiltsetskhlashvili (IBSU Scientific Journal (IBSUSJ), 2009)
The article focuses on recent developments in the former Soviet republics, especially political tremors and hostilities in Caucasus area considerably hinder the development of American businesses in the region. The goal of this study is to investigate factors determining flow of FDI in Georgia, the key point of the analysis is the impact of stability of economic and legal environment on the pattern of FDI. This literary analysis describes the advantages for Georgia to become leader in attracting foreign direct investment (FDI), as well as which sphere are the most effective to develop, which spheres for investment should be given priority, who are the potential investors, how to attract them and what is the most important to which extent will this FDI influence Georgian economy in the long run? The article includes results of a different researches performed to express the progress of the investment and its impact on Georgian economy. The paper also includes results of survey conducted to find out changes of investment climate before and after august conflict and world crisis.
Keywords: 330; foreign direct investment; political and economical stability; domestic market; economic growth